Supervisory Control of Networked Timed Discrete Event Systems With Bandwidth Constraints - Xiang, Zhaoyu; Chen, Yufeng; Wu, Naiqi; Li, Zhiwu (IEEE transactions on automatic control, 2025)
In this article, we investigate the supervisory control of a networked timed discrete event system modeled with a timed automaton. In this system, a plant communicates with its supervisor through multiple observation channels and a single control channel. Any observation channel is imposed a bandwidth constraint such that the number of events transmitted through the channel per time unit should not exceed a given nonnegative integer. The control channel is subject to bounded control delays and losses. Our goal is to synthesize a supervisor against control delays and losses such that the bandwidth constraint of any observation channel is satisfied. To this end, the system is first transformed to a region automaton that is a finite representation of the system's semantics. Then, by considering the impact of control delays and losses on system state estimation, the conventional bipartite transition systems are extended to networked timed ones, from which a necessary and sufficient condition for the existence of a desired supervisor is derived. An algorithm is proposed for building such a supervisor if existing.